Sensitivity of Global Hydrological Simulations to Groundwater Capillary Flux Parameterizations. Issue 1 (19th January 2019) - Koirala, Sujan; Kim, Hyungjun; Hirabayashi, Yukiko; Kanae, Shinjiro; Oki, Taikan
Abstract: Global land surface and hydrologic models, used to quantify the influence of groundwater (GW) dynamics on land surface hydrology, vary in parameterizations of the GW capillary flux and depth of moisture flux exchange between GW and unsaturated soil column (interaction depth). In this study, we demonstrate that the parameterization of capillary flux significantly affects the magnitude of GW‐supported ET (±15%) and GW recharge (±25%). The largest sensitivities are associated with a strong dependence of the capillary flux parameterization on water table depth (WTD) with further controls by soil hydraulic properties. Under shallow WTD condition, the finer soils show a larger GW‐supported ET for parameterization that depends only on WTD. Further, GW‐supported ET reduces by 7–13% per meter increase in interaction depth used in simulation compared to simulation in which the interaction depth varies in space and time with WTD. The simulations of runoff, soil moisture, and WTD are even more sensitive to the difference in parameterization and interaction depth. Moreover, these sensitivities vary largely in both space and time. Evaluations against observation‐based data and previous modeling simulations reveal that simulations with capillary flux perform better than that the one without it in regions with large GW‐supported ET. We concur that capillary flux has a large and nonnegligible influence in global hydrologic simulation. But, the spatiotemporal variabilities of sensitivities of hydrological fluxes and storages demonstrate that different parameterization of GW capillary flux may also lead to a substantial uncertainty in global hydrologic simulations and subsequent water resources assessments. Key Points: The capillary flux significantly alters simulated evapotranspiration and groundwater recharge globally, irrespective of the model parameterization chosen Groundwater‐supported evapotranspiration reduces modeled recharge, runoff, and moisture storages in water resources‐limited regions The sensitivities of hydrologic simulations to model parameterizations of capillary flux depend on water table depth and soil properties